Growth of Sea Grapes (Caulerpa lentillifera) in Laboratory-Scale Cultivation With Urea As A Single Nitrogen Nutrient - Eviana, Maulani; Mukhlis, Alis; Azhar, Fariq (Aquaculture Department, University of Mataram, 2024)
Sea grape (Caulerpa lentillifera) is a strategic green macroalgae with significant potential in aquaculture and functional food industries. However, its cultivation remains constrained by limited production techniques. This study investigated the influence of nitrogen concentration on C. lentillifera growth in a laboratory-scale cultivation system. A completely randomized experimental design was implemented with four treatments: a control group (0 ppm) and nitrogen supplementation levels of 5, 10, and 15 ppm, each replicated thrice over 21 days. Results demonstrated a significant positive correlation between nitrogen concentration and growth parameters. The 15 ppm nitrogen treatment exhibited the highest absolute growth (3.37 g), relative growth rate (13.50%), and specific growth rate (1.82% per day). Interestingly, no statistically significant difference was observed between 10 and 15 ppm treatments, suggesting a potential nitrogen uptake saturation point. Water quality parameters remained stable throughout the experiment, with temperature ranging from 28-30°C, salinity at 33-34 ppt, dissolved oxygen between 5.9-6.7 ppm, and pH maintained at 7.5-7.8. The study provides crucial insights into nitrogen's role in C. lentillifera cultivation, offering a scientific foundation for developing more efficient and sustainable macroalgae production strategies in aquaculture and functional food industries.